The Effectiveness of Using Communicative Activities Games in Improving Students’ Speaking Ability of Grade Eight Students of SMP Muhammadiyah 21 Gantiwarno - Hanifah Nurmalasari (PBI 15 UMY 069, 2015)
*69 The purpose of this research was to know the effectiveness of communicative activities games in improving students of grade eight speaking ability. This research was carried out at grade eight class of SMP Muhammadiyah 21 Gantiwarno in which consisted of 18 students as participant. This research is an experimental research. The data of this research were gathered by speaking test. The research design was quasi exprimental research with non equivalent groups of pretest and posttest. Both the experimental group and control group were selected by random assignment. The effectiveness of using communicative activities games in improving students’ speaking ability of grade eight was proven by the results of computation (from the scores of pretest and posttest). The result of computation showed that the mean score of the students’ speaking test in the control group was 13.1. Meanwhile, the mean score of the students’ speaking test in the experimental group was 18.1. It means that that the mean of test score in experimental group was higher than the mean of test score in control group. Considering the result of effect size, r = 0.69. The value of effect size showed that the effect of communicative activities games was large. Then, the result of hypothesis test could be seen from the value of taccount that is bigger than ttable (3.977>3.426). It means that the researcher’s hypothesis is accepted. So, it is suggested to the English teachers to use communicative activities in improving students’ speaking ability.